TATA AIR PODOLANDAK (Baccaurea sp.), SPESIES JARANG KAWASAN HUTAN TROPIK TERDEGRADASI AKIBAT PENAMBANGAN EMAS DI BOJONGPARI, JAMPANG, PELABUHAN RATU, JAWA BARAT - B. P. Naiola (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Forest exploitation activities always brings some environmental problems such as reduction in individual plant or species biodiversity and some physical deterioration which lead to microclimate change.This study presenting the results of measurement of plant-water relations against a shrub plant (Sundanese) podolakan (Baccaurea sp.),a rare species in a degraded tropical forest land under gold mining pressure in Jampang,Pelabuhan Ratu, West Java.Results shows that no significant differences between plants growing in the degraded and non-degraded (natural) sites in their water relations aspects emphasized on water potential components i.e. total water potential (¥, -MPa): 0,48 and 0,38, osmotic potential (¥„, -MPa):1,64 and 1,44 and turgor pressure (y/p, MPa): 1,16 and 1,06 respectively. The values of their fat turgorloss point showed no significant different either between degraded and natural sites, i.e. -1,93 MPa and -1,43 MPa.Interestingly, in comparison with the dominant species i.e. puspa (Schima wallichii (DC) Korth.) in the non-degraded site, results shows a significant different between these two degraded forest species in their ¥„ (0,01>P>0,001), where there was better developed in the rare species (-1,44 MPa) than the dominant ones (-1,29 MPa). While in the degraded site, there was also a significant different (P<0,001),where the rare species had better development (-1,64 MPa) than the dominant (-0,67 MPa). It seems that the dominant spesies in the degraded site underwent more environmental (water) stress than the rare species as shown by more negative of its Y (-0,82 MPa),while rare species was only -0.48 MPa. Water potentials at turgor loss points were not significantly different between Baccaurea sp. in degraded and natural sites.It is suggested that even though as a rare species, Baccaurea sp.retained better water status. This is maybe due to its position in the forest as lower strata plants, thus received less effect of climatic stress in upper canopy such as more light intensity and bigger wind flow. Hence, in natural reclamation, plant species like Baccaurea sp. may have better chance to role as pioneering species. No significant differences in f at f(turgor loss points) between the degraded and natural sites (-1..93 and -1,43 MPa respectively). It is suggested that water is not a limiting factor for the plants in degraded tropical forest site under gold mining pressure.